Self-Esteem, Anxiety, Locus of Control and Academic Performance Among University Students - Sidhu, Joy (My University, 2018)
ABSTRACT The study was conducted to investigate the relationship on self-esteem, anxiety, locus of control and academic performance among university students. The sample consisted of 120 students (60 males and 60 females). Pearson correlation and t-test were used to analyze the data. The results of the study revealed that there exists a positive relation between self-esteem and academic performance (r=0.78). Negative correlation was found between anxiety (State/Trait) and academic performance (r=-0.41;r=-0.56). No significant relation was found between locus of control and academic performance (r=0.08). Gender differences were found on self-esteem and anxiety but no differences in gender were found for locus of control and academic performance. Keywords: Self-esteem; State Anxiety; Trait Anxiety; Locus of Control; Academic Performance.
Keywords: Self-esteem; State Anxiety; Trait Anxiety Locus of Control; Academic Performance